The emergence of reflexivity in Greek language and thought : from Homer to Plato and beyond - Jeremiah, Edward T. (Philosophia Antiqua, 2012)
Contemporary preoccupation with the self and the rise of comparative anthropology have renewed scholarly interest in the forms of personhood current in Ancient Greece. However the word which translates "self" most literally, the intensive adjective and reflexive morpheme αὐτός, and its critical role in the construction of human being have for the most part been neglected. This monograph rights the imbalance by redirecting attention to the diachronic development of the heavily marked reflexive system and its exploitation by thinkers to articulate an increasingly reflexive and non-dialogical understanding of the human subject and its world. It argues that these two developmental trajectories are connected and provides new insight into the intellectual history of subjectivity in the West.